The Effect of Job Insecurity and Work Stress on Turnover Intention Due to the Impact of Covid-19 on Hero Ambon Hotel - Pieter NR Rehatta; Venska Sitanayah; Saleh Tutupoho (Institute of Computer Science (IOCS), 2022)
This study aims to examine the effect of job insecurity and work stress on turnover intention of Hotel Hero Ambon employees. This type of research is a type of quantitative research using a questionnaire as a research instrument. The sample collection technique in this study used non-probability sampling using all of the population as a sample, namely 33 employees. The analysis technique uses multiple linear regression using SPSS software. Based on the results of hypothesis testing, it was found that the value oft variable job insecurity is 3.675 > t table 2.042 while the significance value is 0.001.These results can be interpreted as a significance value smaller than 0.05 which indicates that Job Insecurity has a significant effect on Turnover Intention, while work stress has a significant effect on turnover intention.t test of work stress variable is2,155> t table 2.042 while the significance value is 0.039. These results can be interpreted that the significance value is smaller than 0.05, so it can be concluded that work stress has a significant effect on turnover intention. The hypothesis in this study which states that job insecurity has a positive and significant effect on turnover intention, acceptance and job stress have a positive and significant effect on turnover intention, accepted.